2016
DOI: 10.1111/jgh.13258
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis B virus in the Philippines

Abstract: Multiple studies have shown a high prevalence of chronic hepatitis B (CHB) infection in the Philippines, not only in high-risk populations but also in the general population. The most recent national study estimated HBsAg seroprevalence to be 16.7%, corresponding to an estimated 7.3 million CHB adults. The factors underlying the high prevalence of CHB and its sequelae include the inadequate use of vaccination for prevention and the lack of treatment for many Filipinos. Because without medical monitoring and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…An international survey, carried out in the Philippines, found that the high prevalence rates of infection with the hepatitis B virus were related to a lack of prevention, through vaccines, and effective treatment, when necessary. Thus, it is emphasized the need for better training of health professionals (26) for actions that make it possible to increase vaccine coverage, such as Hepatitis B, in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…An international survey, carried out in the Philippines, found that the high prevalence rates of infection with the hepatitis B virus were related to a lack of prevention, through vaccines, and effective treatment, when necessary. Thus, it is emphasized the need for better training of health professionals (26) for actions that make it possible to increase vaccine coverage, such as Hepatitis B, in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, prevalence estimates of chronic HBV infection range from approximately 850 000 to more than 2 million cases. 1,[18][19][20] In the United States, new cases of HBV among adults are largely transmitted through injection drug use or sexual intercourse, but most prevalent cases of HBV infection are chronic infections from exposure occurring in infancy or childhood. Another major risk factor for HBV infection is country of origin.…”
Section: Burden Of Diseasementioning
confidence: 99%
“…Statistics show that the seafarers' labour market is dominated by Filipinos, who constitute up to 80% of all employees [7,8]. Interestingly, the Philippines is the country with one of the highest rates of HBV infections in the world, where 16.7% of the general adult population are HBsAg positive, which corresponds to 7.4 million chronically infected people [9].…”
Section: Discussionmentioning
confidence: 99%